Amplifiers and oscillators : optimization by simulation - Dieuleveult, Francois de (ISTE Press ; Elsevier, 2018)
Amplifiers and Oscillators Optimization by Simulation provides a comprehensive resource on the topic, including theory and simulation. The book presents a panorama of electronic patterns, from the simple, to the more complicated. Comparisons of different structures and their advantages and disadvantages are included, making this the go-to book for engineers who need to quickly find the characteristics of a circuit and the method of calculation and dimensioning of components that fit a particular design.